Hubungan Frekuensi Hospitalisasi dengan Kecemasan Anak Leukemia Usia Pra Sekolah Saat Dilakukan TindakanInvasif di RSUD Dr. Moewardi - Susanti, Evy Tri, Siti Arif, Endang Zulaicha, S.Kp (2013)
Special problems of acute lymphoblastic leukemia (LLA) in children is the difference frequency of hospitalization due to stage a series of chemotherapy which requires the child to undergo treatment in hospital. During the treatment the child, the child generally require invasive measures for the recovery process. However, this invasive procedure is often cause anxiety in children. The objective of research is know correlation frequency of hospitalization with anxiety leukemia pre-school age children when performed invasive procedure at Dr. Moewardi hospital. Kind of research is quantitative correlative, with descriptive method, design research is cross sectional approach. Sample research is 16 children, taking sample was using total sampling. Criteria sample is leukemia limfoblastik acut children with age 3-6 years old. instrument variable frequency of hospitalization was using questionnaires, and anxiety using a check list. Data analysis was using Spearman's Rho test. Results showed a correlation coefficient (τ) of - 0.505 with a significance value (p-value) 0.046. result research showed : (1) The majority of acute lymphoblastic leukemia children pre-school age to undergo frequent hospitalization frequency that is equal to 50%. (2) The majority of acute lymphoblastic leukemia children pre-school age are experiencing anxiety that is equal to 43.75%. (3) There was a significant correlation frequency of hospitalization with acute lymphoblastic leukemia child anxiety when performed invasive procedure at Dr. Moewardi Surakarta Hospital.